The Development and Economy of Cybersport, Cybersport Tournaments and its Spatial Effects in Tourism - Olimov Davron Olimovich (Scientific Trends, 2023)
This article is written about the development of cybersport, its advantages, features and effects of cybersport in the tourism industry.
Keywords: Cybersport, Esports, Tourism, Cybersport tournaments.